Contribution of Parental Support and Peer Influence to Student Career Decision Making - Offando, Ocen; Sukma, Dina (Bisma The Journal of Counseling, 2024)
Career development is influenced by various factors. Parental support and peer influence have a strong influence on adolescent career choices. This study aims to analyze the contribution of parental support and peer influence to career decision making. This study uses a descriptive quantitative approach with a correlational method. A total of 151 grade XII students were selected through proportional random sampling techniques to participate in this study. The instruments used include a scale of parental support, peer influence, and career decision making. This study first conducted a Pearson correlation test to determine the contribution between research variables. Then the researcher conducted a classical assumption test as a prerequisite for regression analysis, using normality, linearity, and multicollinearity tests. Data analysis in the hypothesis test used multiple regression using SPSS 23. The results showed that parental support was in the high category, peer influence was in the high category, and career decision making was in the moderate category. The findings in this study indicate that parental support and peer influence contribute significantly to students' career decision making.